Degterev, D.A. Applied Quantitative Analysis and Formal Models of International Relations: Course Textbook. Moscow: RUDN, 2016. 556 p. (in Russian) (Сравнительная политика)
Degterev, D.A. Applied Quantitative Analysis and Formal Models of International Relations: Course Textbook. Moscow: RUDN, 2016. 556 p. (in Russian).